2011
DOI: 10.1163/187847511x570817
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Viewpoint Jitter Shakes Sensory Conflict Accounts of Vection

Abstract: Sensory conflict has been used to explain the way we perceive and control our self-motion, as well as the aetiology of motion sickness. However, recent research on simulated viewpoint jitter provides a strong challenge to one core prediction of these theories -that increasing sensory conflict should always impair visually induced illusions of self-motion (known as vection). These studies show that jittering self-motion displays (thought to generate significant and sustained visual-vestibular conflict) actually… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 81 publications
(69 citation statements)
references
References 69 publications
3
64
2
Order By: Relevance
“…The present result also shows that the amount of vection facilitation caused by the roll jitter did not vary with jitter size; the large jitter and small jitter facilitated vection to an almost equivalent level. The result is consistent with previous studies that have confirmed that the effect of the jitter is very robust against variation of features of the jitter including its amplitude (e.g., Palmisano et al, 2011). Moreover, previous experiments revealed that jitter can facilitate vection only in conditions where it has a component orthogonal to the main-axis motion of the visual inducer (e.g., Nakamura, 2010;Palmisano et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…The present result also shows that the amount of vection facilitation caused by the roll jitter did not vary with jitter size; the large jitter and small jitter facilitated vection to an almost equivalent level. The result is consistent with previous studies that have confirmed that the effect of the jitter is very robust against variation of features of the jitter including its amplitude (e.g., Palmisano et al, 2011). Moreover, previous experiments revealed that jitter can facilitate vection only in conditions where it has a component orthogonal to the main-axis motion of the visual inducer (e.g., Nakamura, 2010;Palmisano et al, 2008).…”
Section: Resultssupporting
confidence: 92%
“…Most previous studies have used simple computer-generated 3-D cloud (or dot motion) displays to generate optic flow simulating self-motion in depth (see Palmisano et al, 2011, for a review). These displays were not designed to simulate the reflectance properties of natural surfaces.…”
Section: Methodsmentioning
confidence: 99%
“…However, several recent studies appear to show that visually induced vection is surprisingly tolerant to a number of so-called "sensory conflict" situations Ash et al 2011a;Ash et al 2011b;Palmisano 2008, 2010;Palmisano et al 2011). For example, we have found that compelling vection can still be induced even when visual and non-visual self-motion stimulations are 180 degrees out-of-phase or indicate self-motion along completely different axes .…”
Section: Experience?mentioning
confidence: 99%